Past, Present and Future of TKA: An Expert Opinion or Point of View - Bernardin, Saccomanni (Archives of Clinical and Medical Case Reports, 2026)
Total knee arthroplasty (TKA) has come a long way from the first resection arthroplasty performed by Ferguson in 1861 to the cutting-edge technology utilized today. From removing bone to improvement function, to interposition arthroplasty in 1863, and introducing an ivory hinged prosthesis fixed with Plaster of Paris in 1891, it has indeed been a checkered journey. The mid-20th century saw the introduction of the metallic mold hemiarthroplasties fitted to femoral condyles and hinged prosthesis made initially of acrylic and then cobalt chromium, which were used till the late 1960s. Their high failure rate was on account of large bony resections and lack of sound kinematics.